Pengembangan E-LKPD Berbasis STEAM-Project untuk Meningkatkan Literasi Kimia Peserta Didik pada Materi sistem Koloid - Susanti, Susanti; Husain, Halimah; Herawati, Netti (Chemistry Education Review (CER), 2024)
This study aims to; 1) Describe the steps of developing STEAM-Project-based E-LKPD to improve students' chemical literacy on colloidal system material, and 2) Describe the validity, practicality, and effectiveness of STEAM-Project-based E-LKPD in improving students' chemical literacy on colloidal system material. This type of research is Research and Development (R&D). Learning activities follow the syntax of the STEAM-Project learning model which begins with determining fundamental questions, designing projects, monitoring the activeness and progress of students' projects, then assessing the results. The research subjects were 33 students of class XI MIPA 7 SMA Negeri 9 Gowa in the 2023/2024 academic year. This research uses Thiagarajan's 4D development model which consists of 4 stages, namely the Define stage, Design stage, develop stage, and disseminate stage. However, this research is limited only to the Develop stage for certain considerations. The instruments used in this study are validity instruments in the form of instrument validation sheets, practicality instruments in the form of teacher response questionnaires, student questionnaires, and implementation questionnaires, and effectiveness instruments in the form of evaluation tests. The results of the study obtained; 1) the product validation index of 0.88 with very valid criteria, 2) the average percentage of product practicality from the responses of teachers and students in the small-scale trial stage.